2023
DOI: 10.1002/adtp.202200320
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin‐Loaded Microneedles Produced Using 3D‐Printed Molds for Klebsiella Pneumoniae Biofilm Control

Abstract: Additive manufacturing advancements contribute considerably to several fields and its use in the medical field is gaining attention due to its easily customizable option (patient-specific), low cost, and fast turnout time in developing drug delivery and diagnostic tools. Herein, the fabrication of a microneedle (MN) platform is reported using a stereolithography 3D printer, varying the 3D printing angle and aspect ratio (2:1, 3:1, and 4:1). The optimal printing angle is 30°, resulting in needle tip and base di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Casting is followed by a solidification step to form the MNs, which can then be peeled from these molds. 73,86 Some polymers may further require cross-linking to improve mechanical strength, control the swelling behavior, or enhance MN stability. 87 Sensor-Integrated Microneedles.…”
Section: ■ Types Of Microneedles For Monitoring Approaches and Their ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Casting is followed by a solidification step to form the MNs, which can then be peeled from these molds. 73,86 Some polymers may further require cross-linking to improve mechanical strength, control the swelling behavior, or enhance MN stability. 87 Sensor-Integrated Microneedles.…”
Section: ■ Types Of Microneedles For Monitoring Approaches and Their ...mentioning
confidence: 99%
“…Swellable MNs are typically fabricated by casting/molding swellable polymers into PDMS master molds with an inverse geometry of the MNs. Casting is followed by a solidification step to form the MNs, which can then be peeled from these molds. , Some polymers may further require cross-linking to improve mechanical strength, control the swelling behavior, or enhance MN stability …”
Section: Types Of Microneedles For Monitoring Approaches and Their Ma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported the fabrication of a microneedle platform using an SLA 3D printer, varying the 3D printing angle and aspect ratio. The investigators concluded that the optimal printing angle was 30°, resulting in needle tip and base diameters of ≈50 and ≈330 μm and heights of ≈550/850/1180 µm [299]. Yang et al developed 3D-printed morphology-customized microneedles with excellent transdermal drug delivery efficiency [300].…”
Section: Materials Jetting (Mj)mentioning
confidence: 99%
“…Another study reported the fabrication of a microneedle platform using an SLA 3D printer, varying the 3D printing angle and aspect ratio. The investigators concluded that the optimal printing angle was 30 • , resulting in needle tip and base diameters of ≈50 and ≈330 µm and heights of ≈550/850/1180 µm [293]. Yang et al developed 3D-printed morphology-customized microneedles with excellent transdermal drug delivery efficiency [294].…”
Section: Materials Jetting (Mj)mentioning
confidence: 99%